R post-vocalique et histoire de l’anglais - Jacques Durand (Anglophonia)
In this paper, I explore the way in which a different norm emerged in England and in the United States concerning the pronunciation of post-vocalic r’s: the R. P. norm (or ‘BBC English’ in the terms of Roach and Hartman’s 1997 edition of Daniel Jones’ English Pronouncing Dictionary) is non-rhotic, whereas the US norm (or ‘Network English’ for the same authors) is rhotic. While the loss of post-vocalic r’s does require an explanation in phonetic and phonological terms, I mainly concentrate on broader sociolinguistic and sociohistorical issue: on the one hand, the early emergence in Britain of London and the surrounding counties as a centre from which changes radiate across the whole of Britain; on the other hand, the complex evolution of English in the United States with the emergence of new social and geographical boundaries. The paper will attempt to show that, while the selection of particular traits to separate dialects is usually arbitrary from a strict linguistic point of view, once a trait has been selected and functions as a ‘shibboleth’ in the Biblical sense (Judges, xii, 5-6, “King James Version”, 1611) powerful societal forces can conjoin to maintain and reinforce it. The role of London vs. New York in explaining rhoticity in Britain and the United States will be seen as a fundamental one.